2019
DOI: 10.1088/1755-1315/403/1/012101
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing the wear of precision pairs of fuel injection equipment in diesel engines

Abstract: Reliable operation of a diesel engine largely depends on wearing degree of joints and assemblies of fuel injection equipment. The precision components of the high-pressure fuel pump and nozzles are most susceptible to wear. The following methods are used to reduce the wear of precision pairs of a high-pressure fuel pump: increasing the hardness of the mating parts, improving the filtering quality of the fuel and increasing the fuel lubricity. From the point of implementing easiness and obtaining the greatest e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The data obtained indicate that the new plunger pairs have lower reliability indicators and a reduced service life. It can be concluded that there is an increased gap between the contacting parts [1,2].…”
Section: Design Methods Operation Methods Technological Methodsmentioning
confidence: 99%
“…The data obtained indicate that the new plunger pairs have lower reliability indicators and a reduced service life. It can be concluded that there is an increased gap between the contacting parts [1,2].…”
Section: Design Methods Operation Methods Technological Methodsmentioning
confidence: 99%
“…• the use of additives that reduce the activity of fuel methanols [38]; • reduced wear of precision pairs of the fuel system [39]; and • periodic flushing of the fuel system [40,41].…”
Section: Introductionmentioning
confidence: 99%